PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOX EDU UNTUK MENINGKATKAN KEMAMPUAN NUMERASI SISWA TUNAGRAHITA - Syarifuddin Syarifuddin; Achmad Hidayatullah; Lala Anggraini (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Students with intellectual disabilities generally face significant challenges in mathematics, such as number recognition, counting, sequencing, basic arithmetic operations, and other functional numeracy tasks, due to their limited memory, abstract reasoning, and information processing speed.Â This study aims to develop the Smart Box Edu learning tool to help students with intellectual disabilities improve their abilities in number recognition, counting, and performing basic operations in mathematics. The study employed the Research and Development (R&D) method using a simplified Borg & Gall model, comprising the following stages: needs analysis, design, development, expert validation, practicality testing, and effectiveness testing. Validation results indicated the medium falls into the “highly suitableâ€ category, with an 88% score from the media expert and a 90% score from the content expert, yielding an average of 89%. The practicality test conducted by two teachers yielded an average score of 89%, while student engagement reached 87%, indicating that the media is highly practical and engaging to use. Effectiveness was assessed through a pretest–posttest on 8 students with moderate and mild intellectual disabilities, with the average score increasing from 40.5 to 77.8, representing a 92% improvement. The N-Gain calculation of 0.63 indicates a moderate level of effectiveness. The study concluded that the Smart Box Edu is a viable, practical, and effective multisensory numeracy tool capable of improving the focus, motivation, and conceptual understanding of numeracy among students with intellectual disabilities. This tool is recommended for use in special education schools and for further development to include other mathematics topics.